Solder Paste

By using 85% to 92% by weight of solder paste combined with a tin-based solder and a modified natural resin, the problems of electromigration and dendritic formation during the soldering process are solved, and the stability of the solder joints and the reliability of the connection are achieved.

CN114728382BActive Publication Date: 2025-05-02ヘレウス エレクトロニクス ゲーエムベーハー ウント カンパニー カーゲー
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080079875.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-10
Filing Date
2020-09-04
Publication Date
2025-05-02
Estimated Expiration
2040-09-04

AI Technical Summary

Technical Problem

The existing no-cleaning solder paste is prone to electromigration and dendritic formation during the welding process, resulting in undesirable short circuits.

Method used

A solder paste consisting of 85% to 92% by weight of tin-based solder and 8% to 15% by weight of flux, which contains 30% to 50% by weight of a modified natural resin combination, 5% to 20% by weight of low molecular carboxylic acid and 0.4% to 10% by weight of amine.

Benefits of technology

The electromigration of solder joints and dendritic formation tendency is significantly reduced, and the frequency of short circuits is reduced, thereby improving the connection stability between electronic components and substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003648472810000081
    Figure BDA0003648472810000081
  • Figure BDA0003648472810000082
    Figure BDA0003648472810000082
Patent Text Reader

Abstract

A solder paste consisting of 85 to 92 wt % of a tin-based solder and 8 to 15 wt % of a flux, wherein the flux comprises i) 30 to 50 wt % of a combination of at least two optionally modified natural resins, based on the total weight of the flux, ii) 5 to 20 wt % of at least one low molecular weight carboxylic acid, based on the total weight of the flux; and iii) 0.4 to 10 wt % of at least one amine, based on the total weight of the flux, and wherein the combination of the optionally modified natural resins has an integrated molecular weight distribution of 45 to 70 area % in the molecular weight range of 150 to 550 in combined GPC and an integrated molecular weight distribution of 30 to 55 area % in the molecular weight range of >550 to 10,000.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a solder paste, in particular for attaching electronic components to substrates.

[0002] Solder pastes, in particular soft solder pastes, are primarily used in the manufacture of electronic circuits and for producing a mechanical, electrical and thermal connection between an electronic component and a substrate, more precisely between the contact surfaces thereof provided for this purpose.

[0003] Examples of electronic components in the sense of the present patent application include diodes, LEDs (light emitting diodes), dies, IGBTs (insulated gate bipolar transistors, bipolar transistors with insulated gate electrodes), MOSFETs (metal oxide semiconductor field effect transistors), ICs (integrated circuits), sensors, heat sinks, resistors, capacitors, coils, connecting elements (e.g., clips), base plates, antennas, etc.

[0004] Examples of substrates in the sense of this patent application include lead frames, PCBs (printed circuit boards), flexible electronics, ceramic substrates, metal ceramic substrates such as DCB substrates (direct copper bonded substrates), IMS (insulated metal substrates) and the like.

[0005] The electronic components are usually contacted with or applied to the substrate via solder paste. The solder paste is heated by a reflow process to melt the solder in the paste, thereby forming contact between the electronic components and the substrate. After the solder is cooled and solidified, the electronic components and the substrate are firmly connected to each other.

[0006] Solder pastes usually contain fluxes, which serve, among other things, to dissolve oxide layers on the surfaces of solder powder, components and substrates and thus ensure better wettability during the soldering process. Since, in the automated production of electronic circuits, solder pastes are processed primarily in screen printing and stencil printing, the fluxes usually additionally contain substances, such as surfactants and additives, which improve the rheological properties of the flux and thus of the solder paste.

[0007] After the soldering process, solder residues originating from the flux remain on the electronic components, which in the case of so-called no-clean solder pastes do not need to be removed from the soldered components. However, there is a tendency for electromigration and / or dendrite formation originating from the solder joints, leading to undesired short circuits. Especially in the course of progressive miniaturization, the problem of electromigration and / or dendrite formation is becoming increasingly important, since the proximity of electronic components that must be kept electrically insulated from one another is increasing at the same time.

[0008] It is an object of the present invention to provide a no-clean solder paste having a reduced tendency or no tendency for electromigration and / or dendrite formation of solder joints formed therefrom.

[0009] The Applicant has been able to develop a solder paste that achieves this object with a new, specifically composed flux, characterized in that at least two natural resins are present simultaneously, the natural resins being particularly characterized with respect to their average molecular weight (M w ) are different from each other and can be optionally modified.

[0010] Therefore, the present invention provides a solder paste, which is composed of 85 wt % to 92 wt % (weight percentage) of tin-based solder and 8 wt % to 15 wt % of flux, characterized in that the flux contains

[0011] i) 30% to 50% by weight, based on the total weight of the flux, of a combination of at least two optionally modified natural resins;

[0012] ii) 5 to 20 wt. %, based on the total weight of the flux, of at least one low molecular weight carboxylic acid; and

[0013] iii) 0.4 to 10 wt. % of at least one amine, based on the total weight of the flux, wherein the combination of optionally modified natural resins has an integrated molecular weight distribution in the molecular weight range of 150 to 550 in a combined GPC (gel permeation chromatography) of 45 to 70 area % and an integrated molecular weight distribution in the molecular weight range of >550 to 10,000 of 30 to 55 area %.

[0014] GPC, including combined GPC mentioned in the form of integrated molecular weight distribution, can be recorded in a conventional manner known to the person skilled in the art, for example according to DIN 55672-1 (March 2016), using crosslinked polystyrene as stationary phase, tetrahydrofuran as liquid phase and polystyrene standards at a temperature of 23°C.

[0015] Unless otherwise stated, all standards cited in this patent application are in each case the version current at the priority date.

[0016] The solder paste according to the invention contains 85 to 92 wt % of tin-based solder.

[0017] The term "tin-based solder" refers to a soldering alloy comprising at least 80% by weight, preferably at least 83% by weight, in particular 85% to 90% by weight, of tin.

[0018] In a preferred embodiment, the solder alloy comprises 0.1 to 8 wt. %, preferably 0.2 to 6 wt. %, of silver, and / or 0.1 to 1.5 wt. %, preferably 0.2 to 1 wt. %, of copper.

[0019] Further preferred are embodiments wherein the solder alloy is lead-free.

[0020] Particularly preferably, the solder alloy contains or consists of tin and silver and copper in the abovementioned ratios.

[0021] Preferably, the solder alloy has a liquidus temperature in the range of 200°C to 250°C, preferably in the range of 200°C to 230°C.

[0022] In a preferred embodiment, the tin-based solder is present in the form of a solder powder, preferably having a weight average particle size of 15 μm to 50 μm, preferably 20 μm to 45 μm, as determined according to IPC-TM-650 2.2.14.2.

[0023] The solder paste according to the invention contains 8 to 15% by weight of flux. This novel flux contained by the solder paste according to the invention itself contains in each case, in sequence, based on its weight, i) 30 to 50% by weight of a combination of at least two optionally modified natural resins, ii) 5 to 20% by weight of at least one low molecular weight carboxylic acid, and iii) 0.4 to 10% by weight of at least one amine, wherein the combination of the optionally modified natural resins has an integrated molecular weight distribution of 45 to 70 area% in the molecular weight range of 150 to 550 and an integrated molecular weight distribution of 30 to 55 area% in the molecular weight range of >550 to 10,000 in the combined GPC.

[0024] The flux comprises i) 30 wt. % to 50 wt. % of a combination (mixture) of at least two optionally modified natural resins, based on its total weight. For a person skilled in the art it is not necessary to explain that "modified" means a chemical modification. The optionally modified natural resins may be unmodified or modified natural resins, for example natural resins modified by hydrogenation, dimerization and / or esterification of their carboxyl groups. In particular, the natural resins are natural resins of the rosin resin type, i.e. unmodified or modified rosin resins, for example rosin resins modified by hydrogenation, dimerization and / or esterification of their carboxyl groups.

[0025] As already mentioned, the combination of at least two optionally modified natural resins has an integrated molecular weight distribution of 45 area % to 70 area % in the molecular weight range of 150 to 550 in a common GPC, and an integrated molecular weight distribution of 30 area % to 55 area % in the molecular weight range of >550 to 10,000. In other words, the area % in the molecular weight range of 150 to 550 and the area % in the molecular weight range of >550 to 10,000 add up to 100 area % of the integrated molecular weight distribution in the molecular weight range of 150 to 10,000. The combined GPC for molecular weights below 150 and above 10,000 preferably has no signal for the at least two optionally modified natural resins.

[0026] The at least two optionally modified natural resins of the combination are preferably selected with respect to their average molecular weight M w Preferably, the solder paste is M w At least one optionally modified natural resin in the range of 150 to 550 and M w Combination of at least one optionally modified natural resin in the range of >550 to 10,000. Average molecular weight M w The determination can be carried out in a customary manner known to the person skilled in the art by GPC, for example according to DIN 55672-1 (March 2016, crosslinked polystyrene as stationary phase, tetrahydrofuran as liquid phase, polystyrene standards, 23° C.).

[0027] In addition, the at least two optionally modified natural resins of the combination may differ with respect to their acid number (AN). w (For example, M w The optionally modified natural resins (in the range of >550 to 10,000) may have an acid value in the range of, for example, 1 mg KOH / g to 50 mg KOH / g and have a lower M w (For example, M w The optionally modified natural resin (in the range of 150 to 550) may have an acid value in the range of, for example, 180 mg KOH / g to 280 mg KOH / g.

[0028] The term “acid number” as used in this patent application relates to the acid number which can be determined in accordance with DIN EN ISO 2114 in mg KOH / g (milligrams KOH per gram).

[0029] As component ii), the flux contains 5 to 20% by weight of at least one low molecular weight carboxylic acid, preferably a dicarboxylic acid. Examples include oxalic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid and tridecanedioic acid.

[0030] In one embodiment, the flux of the solder paste according to the invention has an acid value in the range of 85 mg KOH / g to 145 mg KOH / g based on the total flux.The total acid value of this flux results essentially from the acid contributions of components i) and ii).

[0031] As component iii), the flux contains 0.4 to 10 wt% of at least one amine. Examples of amines include N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N-cocoyl-1,3-diaminopropane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane and 1,10-diaminodecane, bis(2-ethylhexyl)amine, bis(2-methylhexyl)amine, diethylamine, triethylamine, cyclohexylamine, diethanolamine, triethanolamine, hydrogenated tallow alkylamine, hydrogenated (tallow alkyl)dimethylamine and hydrogenated bis(tallow alkyl)methylamine.

[0032] Furthermore, the flux may optionally contain one or more thickeners, for example in a total proportion of 1 to 5 wt%, preferably 1.7 to 4.5 wt%. Examples include ethylcellulose, hydrogenated castor oil, glyceryl tri-12 hydroxystearate and modified glyceryl tri-12 hydroxystearate.

[0033] Furthermore, the flux may optionally contain one or more organic solvents, for example in a total proportion of 32% to 46% by weight, preferably 36% to 42% by weight. Examples include diols, alcohols, ether alcohols and ketones which are liquid at 25° C., in particular trimethylpropanol, 1,2-octanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, isobornylcyclohexanol, glycol ethers, 2-ethyl-1,3-hexanediol, n-decyl alcohol, 2-methyl-2,4-pentanediol, terpineol and isopropanol and mixtures thereof. Examples of glycol ethers include monopropylene glycol methyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, monopropylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, monoethylene glycol n-butyl ether, diethylene glycol n-butyl ether, triethylene glycol n-butyl ether, ethylene glycol dimethyl ether, triethylene glycol methyl ether, diethylene glycol dibutyl ether, tetraethylene glycol dimethyl ether and diethylene glycol monohexyl ether and mixtures thereof.

[0034] Furthermore, the flux may optionally contain one or more halogen-containing compounds, for example, in a total proportion of 0.1 to 3 wt %, preferably 0.5 to 2 wt %. Examples include aniline hydrochloride, glutamic acid hydrochloride, diethanolamine hydrochloride, diethanolamine hydrobromide, triethanolamine hydrochloride, triethanolamine hydrobromide and trans-2,3-dibromo-2-butene-1,4-diol.

[0035] The solder paste according to the present invention preferably has a viscosity of 50 Pa·s to 200 Pa·s at 23° C. and 10 s -1 The shear rate is measured using a flat cone rheometer (e.g., Physica flat cone rheometer from Anton-Paar).

[0036] A further subject matter of the present invention is a method for producing a solder paste according to the invention.

[0037] The method for preparing the solder paste according to the present invention comprises the following steps:

[0038] - the components of the mixed flux, in particular components i), ii) and iii); and

[0039] -Add solder powder as described above.

[0040] The addition of solder powder is preferably done in portions while stirring to form a current mixture of flux components, usually without heating.

[0041] The solder paste according to the invention can be used to connect electronic components to substrates. It can also be used to produce solder deposits on substrates.

[0042] When connecting the electronic component to the substrate, the contact surface of the substrate and the contact surface of the electronic component are in contact via the solder paste according to the present invention.

[0043] A method for attaching an electronic component to a substrate using the solder paste according to the present invention may include the following steps:

[0044] a) providing an electronic component having a contact surface,

[0045] b) providing a substrate having a contact surface,

[0046] c) providing a contact surface of an electronic component and / or a contact surface of a substrate with a solder paste according to the invention,

[0047] d) contacting the contact surface of the electronic component with the contact surface of the substrate via the solder paste; and

[0048] e) The solder paste is heated to above the liquidus temperature of the solder, and the solder is subsequently cooled and solidified, forming a tight connection between the electronic component and the substrate.

[0049] Steps a) and b) are self-explanatory and require no further explanation.

[0050] In step c), the solder paste according to the invention can be applied to one or both contact surfaces by means of customary methods known to those skilled in the art, for example by means of screen printing or stencil printing.

[0051] In step d), the contact surfaces of the electronic component and the substrate may be brought into contact with each other via the solder paste. In other words, a sandwich arrangement may be produced by the electronic component and the substrate with the solder paste between their contact surfaces.

[0052] In step e), the sandwich arrangement can be soldered by heating the solder paste to above the liquidus temperature of the solder, so as to produce a strong connection between the electronic component and the substrate via the solder paste after subsequent cooling and solidification of the solder. In this case, the solder paste is preferably heated so that the solder is transformed into its liquidus phase, but without damaging the solder paste, the electronic component and / or the substrate. The sandwich arrangement or the solder paste is preferably heated to a temperature of 5°C to 60°C, preferably 10°C to 50°C, above the liquidus temperature of the solder.

[0053] Electronic modules having electronic components and substrates soldered together according to the attachment method of the present invention have significantly less frequency of short circuit occurrence. This desirable behavior is a result of the reduced or absent tendency of electromigration and / or dendrite formation of solder joints formed in the method of the present invention. Example

[0054] Test methods used :

[0055] 1. Wetting ability :

[0056] The wetting properties of the solder pastes were evaluated using the melt test according to IPC-TM-650 (1 / 95) test method 2.4.45. For this purpose, the solder paste to be tested was applied to a copper sheet (20 mm x 20 mm x 0.5 mm). If the copper sheet had an oxide layer on the surface, it was polished to bare metal with P600 grade sandpaper and cleaned with ethanol. Copper sheets with a bright and pure surface were cleaned only with ethanol.

[0057] The prepared copper sheet is printed with the aid of a stencil. For this purpose, the stencil is firmly pressed against the copper sheet so that the opening in the stencil is in the middle of the copper sheet. The solder paste to be tested is placed on a Japanese scraper and first spread gently and then spread over the opening in the stencil with slightly greater pressure until no more solder paste is left on the stencil. The stencil is then carefully removed to obtain the pattern given by the stencil. The printed copper sheet is placed on a first heating plate set at a temperature of 200°C to below the liquidus temperature of the solder for 2 minutes, and then immediately placed on a second heating plate with a temperature of about 50°C (peak temperature) higher than the liquidus temperature of the solder. After the solder paste or solder melts, the copper sheet is placed on the heating plate for another 5 seconds, then removed and cooled.

[0058] After the solder paste has cooled, an evaluation is made as to whether it has melted into a spot corresponding to the size of the opening in the stencil or into several small spots, and whether the solder paste has a sharp edge after melting. In addition, an evaluation is made as to whether the surface is glossy or matte.

[0059] Solder pastes were classified into four categories, with categories 1 and 2 being classified as satisfactory results, while categories 3 and 4 indicated unsatisfactory results:

[0060] Category 1: The remelted area is larger than the area previously printed with solder paste.

[0061] Category 2: The remelted areas correspond to the areas previously printed with solder paste.

[0062] Category 3: The remelted area is smaller than the area previously printed with solder paste (slight dewetting can be seen).

[0063] Category 4: The solder paste has formed one or more solder balls and has not wetted the copper or has not completely melted.

[0064] 2. Surface Insulation Resistance (SIR) test, corrosion behavior of solder joints

[0065] According to the test method of J-STD-004B:2011, the changes are as follows:

[0066] - Printed circuit boards according to IPC-B-24, line width 200 μm and distance between lines 200 μm,

[0067] -Environmental conditions: 65℃ / 93% relative humidity,

[0068] -100V corrosion voltage, 100V measurement voltage, measurement frequency 60 minutes

[0069] -Test duration 1,000h

[0070] Two criteria are used to evaluate the SIR test:

[0071] Criterion 1 (Visually detectable dendrite formation): A visual inspection was performed as to whether dendrites had formed in the area of ​​the soldered SIR conductor traces when viewed under an optical microscope at a magnification of 25x.

[0072] Criterion 2 (checking for unexpected resistance deficiency every hour, indicating a stability criterion of >100 MΩ): Resistance measurements are made every hour over a total period of 1,000 h. When all resistances measured over that period are >100 MΩ, the result of the SIR test is evaluated as stable. In contrast, when one or more of the 1,000 measurements are ≤100 MΩ, the result of the SIR test is evaluated as unstable.

[0073] Table 1 shows the flux compositions of comparative solder pastes 1 to 6 and solder pastes 7 to 13 according to the invention. The figures in each case refer to wt %. In each case, 11 parts by weight of these fluxes were mixed with 89 parts by weight of solder powder (SnAgCu: Sn 96.5 wt %, Ag 3.0 wt %, Cu 0.5 wt %, type 3 according to standard IPC J-STD-006) in each case to form solder pastes. The properties of the solder pastes were determined by the above-described methods and are also summarized in Table 1.

[0074] Table 1

[0075]

[0076]

[0077] *) The area ratio of the molecular weight in the GPC of the rosin resin / in the GPC of the combination of the rosin resins ranges from 150 to 550 / 551 to 10,000.

Claims

1. A solder paste comprising 85 wt % to 92 wt % of a tin-based solder and 8 wt % to 15 wt % of a flux, wherein the flux comprises i) 30% to 50% by weight, based on the total weight of the flux, of a combination of at least two unmodified or modified natural resins; ii) 5 to 20 wt. % of at least one low molecular weight carboxylic acid, based on the total weight of the flux; and iii) 0.4 to 10 wt. %, based on the total weight of the flux, of at least one amine, and wherein said combination of said unmodified or modified natural resins has an integrated molecular weight distribution of 45 area % to 70 area % in the molecular weight range of 150 to 550 and an integrated molecular weight distribution of 30 area % to 55 area % in the molecular weight range of >550 to 10,000 in a combined GPC, wherein the solder is a solder alloy comprising at least 80 wt. % tin, wherein the at least one low molecular weight carboxylic acid is selected from the group consisting of oxalic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid and tridecanedioic acid, and The at least two unmodified or modified natural resins have a molecular weight M w different, The combination of at least two unmodified or modified natural resins is w At least one unmodified or modified natural resin in the range of 150 to 550 and M w a combination of at least one unmodified or modified natural resin in the range of >550 to 10,000, wherein the flux has an acid value in the range of 85 mg KOH / g to 145 mg KOH / g based on the total weight of the flux, The unmodified or modified natural resin is an unmodified or modified rosin resin. 2 . The solder paste of claim 1 , wherein the solder alloy has a liquidus temperature in the range of 200° C. to 250° C.

3. The solder paste according to claim 1 or 2, wherein the unmodified or modified natural resin is an unmodified rosin resin or a rosin resin modified by hydrogenation, dimerization and / or esterification of their carboxyl groups.

4. The solder paste according to claim 1 or 2, wherein the combined GPC of molecular weight below 150 and molecular weight above 10,000 has no signal for the at least two unmodified or modified natural resins.

5. The solder paste according to claim 1 or 2, wherein the at least two unmodified or modified natural resins differ with respect to their acid values.

6. The solder paste according to claim 5, wherein the solder paste has a relatively high M w The unmodified or modified natural resin has an acid value in the range of 1 mg KOH / g to 50 mg KOH / g and has a lower M w The unmodified or modified natural resin has an acid value in the range of 180 mg KOH / g to 280 mg KOH / g.

7. The solder paste according to claim 1 or 2, wherein the at least one amine is selected from the group consisting of: N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N-cocoyl-1,3-diaminopropane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane and 1,10-diaminodecane, bis(2-ethylhexyl)amine, bis(2-methylhexyl)amine, diethylamine, triethylamine, cyclohexylamine, diethanolamine, triethanolamine, hydrogenated tallow alkylamine, hydrogenated (tallow alkyl)dimethylamine and hydrogenated bis(tallow alkyl)methylamine.

8. The solder paste according to claim 1 or 2, wherein the flux comprises 1 wt% to 5 wt% of one or more thickeners and / or 32 wt% to 46 wt% of one or more organic solvents and / or 0.1 wt% to 3 wt% of one or more halogen-containing compounds.

9. Use of a solder paste according to one of claims 1 to 8 for connecting electronic components to a substrate or for producing a solder deposit on a substrate.

10. A method for attaching an electronic component to a substrate using a solder paste according to one of claims 1 to 8, the method comprising the steps of: a) providing an electronic component having a contact surface, b) providing a substrate having a contact surface, c) providing the solder paste according to one of claims 1 to 8 to the contact surface of the electronic component and / or the contact surface of the substrate, d) contacting the contact surface of the electronic component with the contact surface of the substrate via the solder paste; as well as e) heating the solder paste to a temperature above the liquidus temperature of the solder, and then cooling and solidifying the solder while forming a tight connection between the electronic component and the substrate.

Citation Information

Patent Citations

  • Rosin-free thermosetting flux formulations

    CN106255569A

  • Lead-free solder alloy, flux composition, solder paste composition, electronic circuit board and electronic control device

    CN107427969A

  • Flux composition, solder paste composition, and electronic circuit board

    EP3335829A1

  • Flux and solder paste

    EP3530397A1